The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4186/ej.2012.16.3.45
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Gold Nanoparticles/Polypyrrole/HRP Electrode for Phenol Biosensor by Electropolymerization

Abstract: Abstract.A phenol enzyme biosensor was fabricated in this research using disposable screen-printed carbon electrode modified with gold nanoparticles (AuNPs), polypyrrole (PPy) and immobilized horseradish peroxidase (HRP) by electropolymerization method. The physical and chemical properties of the modified electrode was characterized by scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX) while electrochemical analysis was performed with amperometry. The fabrication parameters, gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Hence, the developed biosensor is suitable for the determination of glucose in human serum samples [33]. Another study using gold nanoparticles electropolymerized with PPy was fabricated as a bioanode by immobilizing horseradish peroxidase (HRP) on PPy polymer matrices for best detection [34,35]. Li et al reported that this particular polymeric device also focused on novel polypyrrole nanotubes (PPy-NTs) derived from methyl orange (MO) was used as matrix to construct a highly responsive phenol bio electrode on polyphenol oxidase (PPO) via the cross-linking in the presence of glutaraldehyde on glassy carbon electrode surface [36].…”
Section: Biosensors and Biofuel Biodevice Applicationmentioning
confidence: 99%
“…Hence, the developed biosensor is suitable for the determination of glucose in human serum samples [33]. Another study using gold nanoparticles electropolymerized with PPy was fabricated as a bioanode by immobilizing horseradish peroxidase (HRP) on PPy polymer matrices for best detection [34,35]. Li et al reported that this particular polymeric device also focused on novel polypyrrole nanotubes (PPy-NTs) derived from methyl orange (MO) was used as matrix to construct a highly responsive phenol bio electrode on polyphenol oxidase (PPO) via the cross-linking in the presence of glutaraldehyde on glassy carbon electrode surface [36].…”
Section: Biosensors and Biofuel Biodevice Applicationmentioning
confidence: 99%
“…The direct adsorption of HRP molecules on electrode surfaces causes denaturation and loss of activity including the slow electron transfer due to the active sites of enzyme have the long distance between the active sites and electrode surface [44]. Therefore, nanomaterials like gold nanoparticles have been applied as a promoter to enhance the electron transfer as was proposed by Kumpangpet et al [45]. Moreover, Imabayaschi et al reported the HRP biosensor constructed by enzyme covalently immobilized on the mercaptonic acid self-assembled monolayer on the gold electrode [39].…”
Section: Horseradish Peroxidase Electrodes For Phenolicmentioning
confidence: 99%